VP126 The Effectiveness And Safety Of Barbed Sutures In Bariatric Surgery. (12th January 2018) - Huang, Jin; Du, Liang; Zhang, Yonggang; Liao, Ga; Lin, Yifei
Abstract : INTRODUCTION: Knotless barbed sutures can eliminate knot tying during the bariatric surgery (BS) (1). Since effects reported by patients and surgeons are ambiguous, the aim of this study was to establish the safety and efficacy of barbed sutures for intestinal sutures to close the gastrojejunal anastomosis in obese patients undergoing BS. METHODS: PubMed, EMBASE, Cochrane Register of Clinical Studies, and ClinicalTrials.gov were searched for randomized controlled trials (RCTs) and cohort studies comparing barbed sutures with conventional sutures in BS (until 30 June 2016). Quality assessment was conducted using to Cochrane recommendations. Review Manager was applied to analyze the data, and we sequentially omitted each study to perform sensitivity analyses. RESULTS: A total of five cohort studies (low to moderate risk of bias) (n = 859), and no RCTs provided eligible patients. BS includes laparoscopic Roux-en-Y gastric bypass and Laparoscopic sleeve gastrectomy. Comparing to conventional sutures, pooling data showed that suture time (Mean Difference, MD = -5.73, 95 percent Confidence Interval, CI -6.25 to -5.21, P < .01) and operative time (MD = - 7.67, 95 percent CI -10.49 to -4.85, P < .01) decreased significantly in the barbed group. Although the postoperative complications did not suggest significant changes (Odds Ratio, OR = 1.56, 95 percent CI .79 to 3.07, P = .2), the pooling results of hospital stay suggested that a significantly longer duration happened in the barbed groups, despite the fact that there may be only 0.18 day longer. (MD =0.18, 95 percent CI .06 to .29, P = .003). CONCLUSIONS: The barbed suture is an effective and safe surgical technique in BS. More evidence with randomized design, larger sample sizes and longer follow up need to compel validations of this state-of-the-art product in the future (2, 3).